Actualización del sistema de fuerza en el banco didáctico de pruebas y arranque de motores trifásicos para prácticas de laboratorio con estudiantes de tecnología e ingeniería de la universidad Antonio Nariño sede Cúcuta, Norte de Santander. - Botello Rangel, Jefferson Arturo (Universidad Antonio Nariño, 2021)
The following work presents the update of the didactic test and start-up bank for three-phase motors for practices with technology and engineering students from the Antonio Nariño University, Cúcuta campus, with the current standards under regulation, RETIE, NTC 2050. The update will be confirmed by a by a board, a 3x20 amp totalizer, three 40 amp contactors with their respective protection for starting the motor, an analog voltmeter, an analog ammeter, two four position selector knobs, a thermal relay, three blue luminaires, one red luminaire, one NC button, one NO button, an analog timer, a digital voltmeter, digital ammeter, three window type current transformers. Different practices of electrical motor connections can be carried out, analyze their behavior, measure variables (voltage, current). The update allowed putting into practice the knowledge acquired both academically and in the workplace in accordance with current regulations, through a design in AUTO CAD and CADe SIMU software was used for the force and command systems of the didactic guides. Finally, laboratory guides are included to carry out practices by students, teachers and laboratory personnel of the Antonio Nariño University.